Consequences of the farming on the image of aquatic products for consumers - Mariojouls C. (Marketing of aquaculture products, 1996)
For the consumers, the products of fisheries have usually a very positive image, because they are regarded as healthy, and coming from the sea, which represents a clean and wide space of freedom, linked with holidays. Aquaculture products also benefit from this positive image, as most of the time, the consumers do not know really their origin, as they often do not know that they are not wild products. We propose some thoughts about the marketing of aquaculture products, through different points: (i) the observation of marketing booklets for salmon, showing two possible attitudes: one based on the valorization of the specific advantages of farmed products, and one with no reference to them, entertaining the confusion with wild products; (ii) the results of a short inquiry about the image of aquaculture products, showing that there are three types of attitude: positive, neutral, negative; (iii) the example of classical animal products, for which appears a differentiation in the markets with the use of designations for products, as an answer to the demand of consumers concerned by animal welfare and natural food; (iv) some thoughts about the utilization of designations for some aquaculture products, as a way to create a segmentation in the market.
Seminar of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1995/10/11-13, Thessaloniki (Greece)